Wearing Diabetes: A cultural analytical approach to the Continuous Glucose Monitor as a symbol of Individual and Collective Identity - Eginoglou,Anastasia (2025)
This master’s thesis is a cultural analysis of individuals with Type 1 diabetes, who use Continuous Glucose Monitors (CGM). It focuses on how these devices shape both individual and collective identities within the diabetes community, and beyond. Using a combination of interviews, observations, and a visual ethnographic approach such as participant-designed sketches, this research explores the role of CGMs as cultural symbols. These devices, far from being emotionless clinical tools, are shown to carry a deeper meaning for users, influencing their personal and interpersonal identities, daily routines, and emotional well-being. By examining CGM users’ experiences about these technologies, the study seeks to uncover how CGMs function as symbols in the creation of communities - both inclusive and exclusive - based on factors such as personal experiences with diabetes, technological adaptation, and cultural context. It also demonstrates that CGMs are not simply medical devices, but are embedded in social and cultural dynamics, fostering a sense of belonging while also defining boundaries within the community of people with diabetes. This research offers insights that can enhance patient care, guide technological advancements, and empower individuals managing diabetes. By focusing on emotional and psychological dimensions often overlooked in traditional research, this study contributes to a more holistic approach to chronic disease management and healthcare innovation.
Keywords: Type 1 diabetes; Continuous glucose monitors (CGM); user experience; symbols; identity; ethnography; medical anthropology; cultural analysis; chronic disease